2020
DOI: 10.3390/ijerph17217742
|View full text |Cite
|
Sign up to set email alerts
|

The Crossover Effects of Supervisors’ Workaholism on Subordinates’ Turnover Intention: The Mediating Role of Two Types of Job Demands and Emotional Exhaustion

Abstract: Although much research has been conducted on workaholism, its crossover effects remain uninvestigated, especially in the context of organizations. Based on the job demands-resources (JD-R) model of burnout and the conservation of resources (COR) theory, we established a dual-path structural model to examine the effects of supervisors’ workaholism on subordinates’ turnover intention through two types of job demands (perceived workload and interpersonal conflict) as well as subordinates’ emotional exhaustion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 106 publications
(166 reference statements)
2
32
0
2
Order By: Relevance
“…Through a self-regulated process, engaged individuals freely choose to perform HWI because they enjoy their job and perceive it as enriching and stimulating [ 61 ]. This result agrees with the definition of work engagement as a harmonious passion, leading individuals to engage in a specific activity that is recognized as meaningful and represents them [ 65 ]. In contrast to workaholic employees, they do not experience an inner urge that compels them to center their existence on work-related activities as the only means for avoiding feelings of worthlessness.…”
Section: Discussionsupporting
confidence: 88%
“…Through a self-regulated process, engaged individuals freely choose to perform HWI because they enjoy their job and perceive it as enriching and stimulating [ 61 ]. This result agrees with the definition of work engagement as a harmonious passion, leading individuals to engage in a specific activity that is recognized as meaningful and represents them [ 65 ]. In contrast to workaholic employees, they do not experience an inner urge that compels them to center their existence on work-related activities as the only means for avoiding feelings of worthlessness.…”
Section: Discussionsupporting
confidence: 88%
“…Namely, job demands can lead to a decrease in self-efficacy. Role ambiguity, role conflict and interpersonal conflict are widely regarded as a kind of hindering job demands (Lorente Prieto et al, 2008 ; Ashill and Rod, 2011 ; Martinez-Corts et al, 2015 ; Kilroy et al, 2016 ; Kim and Beehr, 2018 ; Kim et al, 2020 ). Previous studies have also shown that role ambiguity, role conflict and interpersonal conflict were negatively correlated with individuals' self-efficacy (Jex and Gudanowski, 1992 ; Hartline and Ferrell, 1996 ; Chebat and Kollias, 2000 ; Eys and Carron, 2001 ; Karatepe et al, 2006 ; Li and Bagger, 2008 ; Tang and Chang, 2010 ; Kadir et al, 2017 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…With the rise of workaholism in the Korean society, much research has been carried out to investigate the antecedents and outcomes of workaholism (Jeong & Tak, 2009; Kim et al, 2020; Lee, 2019; Lee & Jung, 2012). However, the lack of reliable and valid measures of workaholism is one of the biggest obstacles to improving workaholism studies in Korea.…”
Section: Workaholism Studies In Koreamentioning
confidence: 99%